ASPECTS OF THE VERBS IN THE UZBEK AND IN THE ENGLISH LANGUAGES - Hamroyeva Umida Mirzohid qizi,; A.Shavkatovich, (Лучшие интеллектуальные исследования, 2024)
Annotation. This article delves into the structural discordances present in English and Uzbek languages, offering detailed examples to illustrate the variations and parallels between them. Specifically, we will explore the utilization of grammatical categories of verbs in both languages.